The Mediating Role of Islamic Spirituality in Shaping Career Interest in Islamic Banking - Mauludi AC, Ali; Fadllan, Fadllan; Haryanti, Nik (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
This study examines Islamic spirituality as an intervening variable mediating the relationship between religiosity, the sharia system, professionalism, and career interest in Islamic banking among students at Islamic higher education institutions in East Java, Indonesia. Employing a quantitative approach, the research utilized purposive and random sampling techniques to survey 150 respondents, determined using the Lemeshow method. Data were analyzed through multiple regression and path analysis within an associative comparative framework. Findings reveal that religiosity and the sharia system lack direct influence on career interest but exhibit significant indirect effects when mediated by Islamic spirituality. Conversely, professionalism directly and positively impacts career interest without requiring spiritual mediation. The study highlights the critical role of Islamic spirituality in amplifying religiosity and sharia adherence to shape career aspirations, while professionalism independently drives career interest. Theoretical implications suggest that Islamic spirituality bridges ideological principles with vocational motivation, whereas practical insights emphasize integrating spiritual values into academic curricula and fostering workplace environments that reinforce sharia compliance. These outcomes underscore the need for Islamic financial institutions to cultivate spiritual motivation among employees to align operational practices with ethical foundations.========================================================================================================ABSTRAK - Peran Mediasi Spiritualitas Islam dalam Membentuk Minat Karir di Perbankan Syariah. Penelitian ini mengkaji spiritualitas Islam sebagai variabel intervening yang memediasi hubungan antara religiositas, sistem syariah, profesionalisme, dan minat berkarir di perbankan syariah pada mahasiswa di perguruan tinggi Islam di Jawa Timur, Indonesia. Dengan pendekatan kuantitatif, penelitian ini menggunakan teknik purposif dan random sampling untuk mensurvei 150 responden, yang ditentukan dengan metode Lemeshow. Data dianalisis melalui regresi berganda dan analisis jalur dalam kerangka penelitian lapangan komparatif asosiatif. Hasil analisis menunjukkan bahwa religiositas dan sistem syariah tidak berpengaruh langsung pada minat berkarir, tetapi memiliki efek tidak signifikan ketika dimediasi oleh spiritualitas Islam. Di sisi lain, profesionalisme berdampak positif secara langsung pada minat berkarir tanpa memerlukan mediasi spiritual. Studi ini menekankan peran krusial spiritualitas Islam dalam memperkuat religiusitas dan kepatuhan syariah untuk membentuk minat karir, sementara profesionalisme secara independen mendorong minat berkarir. Implikasi teoretis menunjukkan bahwa spiritualitas Islam menjembatani prinsip ideologis dengan motivasi vokasional, sedangkan implikasi praktis menyarankan integrasi nilai spiritual dalam kurikulum akademik dan pengembangan lingkungan kerja yang memperkuat kepatuhan syariah. Hasil ini menegaskan pentingnya lembaga keuangan Islam dalam menumbuhkan motivasi spiritual karyawan guna menyelaraskan praktik operasional dengan fondasi etis.